A nyugat-romániai autóipar - a "globális szállító" - Nagy, Csaba (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The cornerstone of the economy of the West-Romanian counties (Timis, Arad, Hunedoara and Caras-Severin) is the automotive industry. The automotive industry’s nature is characterized by constant change, novelty, work on the network (clusters) and the consoli-dation of the component segments: from supplier to consumer. The huge competition manifested in the world’s economy leads to constant fluctuations in the size of relevant businesses, production and staffing levels, costs and income. This phenomenon works like a chain-reaction, affecting other industries, with unpredictable effects. From this results the importance of this industry, prone to migration. Economic crisis strongly influences the automotive industry, but nevertheless, its proportion remains significant in the West-Romanian economy.- Its products travel round the world, so it is often referred to as "global supplier".